VITAMIN D AND BODY MASS INDEX IN GESTATIONAL DIABETES MELLITUS - Simeonova krstevska, Slagjana; Samardjiski, Igor; Irena Todorovska; Sima, Aneta; Livrinova, Vesna; Jovanovska, Viktorija (Department of Anaesthesia and Reanimation, Faculty of Medicine, “Ss. Cyril and Methodius” University in Skopje, R.N.Macedonia, 2021)
ABSTRACT Gestational diabetes mellitus (GDM) is a glucose intolerance established for the first time in pregnancy. Vitamin D deficiency is common in pregnant women. Deficiency is connected with risk for preeclampsia, GDM and macrosomia. Aim Aim of the study was to evaluate vitamin D status in GDM pregnancies and normoglycemic women and to establish whether body mass index in normoglycemic and GDM pregnant women has impact on vitamin D deficiency. Material and Methods Prospective study was conducted at the University Clinic for Gynecology and Obstetrics, Skopje in a period of one year. One hundred pregnant women in the second trimester were evaluated: 50 women with GDM and a control group of 50 women with negative OGTT with BMI more or less than 25. Vitamin D levels (Advia Centaur) were performed from periphery blood specimens from the pregnant women. Results Significantly lower values of vitamin D were found in GDM women vs control group (16.91 ± 6.2 nmol/l vs 24.54 ± 11.7 nmol/l). Vitamin D deficiency was found in 82.5% of the women with GDM and 54.76% of the women with negative OGTT. Vitamin-mineral supplementation received 82% of the normoglycemic pregnant women and 66% of the pregnant women with GDM, p=0.036. In pregnant glucose tolerant women vitamin D was significantly lower in overweight vs normal weight women. Women with GDM and normal weight had significantly lower vitamin D levels vs normoglycemic women with normal weight. Conclusion We can conclude that gestational diabetes mellitus in our study is associated to lower values of vitamin D. Pregnant women with GDM less often received vitamin supplementation. Lower vitamin D levels were found in normoglycemic overweight women. In GDM women body mass index didn’t have impact on vitamin D deficiency – normal weight GDM women had significantly lower vitamin D levels than normoglycemic women with normal weight. However, vitamin D supplementation is essential for overweight pregnant women in order to possibly achieve better perinatal outcome.
Keywords: BMI; gestational diabetes mellitus; vitamin D